2023
DOI: 10.1088/1742-6596/2424/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

The Low-light License Plate Recognition via CNN

Abstract: The low-light license plate recognition (LPR) is an important task in LPR, and the task of low-light LPR is a challenge in LPR. Compared with ordinary LPR, low-light LPR is more challenging. The first is that there are few studies on low-light LPR, and there is a lack of dedicated datasets. Besides, there are few lightweight networks dedicated to low-light LPR. The lack of lightweight private networks makes it difficult to deploy LPR methods efficiently. Based on this, this paper proposes a low-light LPR metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the past five years, license plate recognition technology has developed rapidly at home and abroad. [1,2] In the process of consulting many related literatures, the author found that most of the researchers are studying the fundamental recognition principle of license plate recognition technology, such as A. Hendry and R.-C [3] , X. Zhou [4] ,X. Qin [5], L. Du [6], D. V. Niture [7] , R. Gomes [8] ,S. Zherzdev and A. Gruzdev [9], A. Khan [10], K. Abebe [11] and other authors proposed a variety of efficient license plate recognition techniques and methods, and discussed the application of neural convolution network technology in the field of license plate recognition from different perspectives. These provide many improvement ideas for the author's research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In the past five years, license plate recognition technology has developed rapidly at home and abroad. [1,2] In the process of consulting many related literatures, the author found that most of the researchers are studying the fundamental recognition principle of license plate recognition technology, such as A. Hendry and R.-C [3] , X. Zhou [4] ,X. Qin [5], L. Du [6], D. V. Niture [7] , R. Gomes [8] ,S. Zherzdev and A. Gruzdev [9], A. Khan [10], K. Abebe [11] and other authors proposed a variety of efficient license plate recognition techniques and methods, and discussed the application of neural convolution network technology in the field of license plate recognition from different perspectives. These provide many improvement ideas for the author's research in this paper.…”
Section: Introductionmentioning
confidence: 99%